The new separation of powers a theory for the modern state - Carolan, Eoin. (Oxford Oxford University Press, 2009)
The separation of powers is an important principle of liberal constitutionalism. However, the traditional rationale behind institutional separation can no longer govern the distribution of authority in the modern state.
Includes bibliographical references (p. [267]-272) and index.
Keywords: Separation of powers--Ireland.